Impact of teacher-gender on primary students’ achievement: a study at Malaysian standpoint - Hoque, K.E.; Razak, Ahmad Zabidi Abdul; Zohora, M.F.; Islam, R. (Macrothink Institute, 2013)
This study attempts to find the impact of teacher-gender on primary student achievement. The quantitative method of research was used for this study. This study, first in its nature in Malaysia, uses test scores of primary grades for five consecutive years which is obtained from a school in Kuala Lumpur. This study engages a total of 1 school, 20 classes, 30 teachers and 604 students. The overall finding in this study is that women are slightly better to teach in primary when the test scores are analyzed. Although there are some differences in the breakdown analysis, the combined result analysis do not find strong evidence to claim whether students have to be taught by teachers of same or alternative gender. The findings of this study provide important information for the policy makers and especially for the primary teachers’ recruiters in primary schools of Malaysia.